2022
DOI: 10.1007/s41669-022-00338-2
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Olaparib in Combination with Bevacizumab Compared with Bevacizumab Monotherapy for the First-Line Maintenance Treatment of Homologous Recombination Deficiency-Positive Advanced Ovarian Cancer

Abstract: Background In the PAOLA-1 trial, olaparib plus bevacizumab demonstrated significant clinical benefit following partial or complete response to platinum-based chemotherapy in homologous recombination deficiency (HRD)-positive ovarian cancer. Our study evaluated the cost effectiveness of olaparib plus bevacizumab compared with bevacizumab alone as a maintenance treatment for women in this population. Methods Our model was a cohort-level partitioned survival model with a lifetime horizon from a US healthcare syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Characteristics of the included studies are shown in presented in S2 Table . Overall, 19 studies were published after June, 2019, including 9 in 2020 [ 22 30 ], 7 in 2021 [ 31 37 ], and 3 2022 [ 38 40 ]. Studies were conducted from the United States (US) (n = 13) [ 16 – 20 , 23 28 , 38 , 40 ], China (n = 5) [ 27 , 30 , 32 , 39 , 40 ], Singapore (n = 2) [ 31 , 34 ], Japan [ 21 ], Italy [ 22 ], and Spain [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the included studies are shown in presented in S2 Table . Overall, 19 studies were published after June, 2019, including 9 in 2020 [ 22 30 ], 7 in 2021 [ 31 37 ], and 3 2022 [ 38 40 ]. Studies were conducted from the United States (US) (n = 13) [ 16 – 20 , 23 28 , 38 , 40 ], China (n = 5) [ 27 , 30 , 32 , 39 , 40 ], Singapore (n = 2) [ 31 , 34 ], Japan [ 21 ], Italy [ 22 ], and Spain [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 19 studies were published after June, 2019, including 9 in 2020 [ 22 30 ], 7 in 2021 [ 31 37 ], and 3 2022 [ 38 40 ]. Studies were conducted from the United States (US) (n = 13) [ 16 – 20 , 23 28 , 38 , 40 ], China (n = 5) [ 27 , 30 , 32 , 39 , 40 ], Singapore (n = 2) [ 31 , 34 ], Japan [ 21 ], Italy [ 22 ], and Spain [ 33 ]. PARPi evaluated in these studies included olaparib [ 16 – 18 , 20 22 , 25 28 , 30 32 , 34 40 ], niraparib [ 18 20 , 23 , 26 , 28 ], rucaparib [ 20 , 28 ], talazoparib [ 33 ], and veliparib [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations